Teknik Pemasaran dan Pengelolaan Sistem Keuangan pada UMKM Rosalia (Olahan Salak) di Era Pandemic Covid-19 - Hanifah Rahmi Fajrin; Puspita Dewi Wulaningrum; M. Mulki Sulaiman (Jurnal Pemberdayaan Masyarakat, 2022)
One of the impacts of the Covid-19 pandemic on the economic sector is the cessation of production activities in various businesses, falling levels of consumption and consumer confidence in a product. Rosalia is one of the small and medium business units engaged in the food sector, in the form of processed Salak products. The pandemic situation has also resulted in MSMEs being devoid of buyers, resulting in decreased income from business owners. Therefore, a marketing strategy is needed that can help this business to survive. One of the marketing techniques that will be applied is the use of social media and the creation of online shop accounts in marketplaces such as Shopee and business Instagram accounts. In addition, to ensure that the financial recording system in MSMEs is neatly organized, training on financial management will be given